Breve retrato do secretariado administrativo/executivo virtual em Portugal - Correia, Andreia Raquel Fonseca (2022)
The emergence of new information and communication technologies (ICT) has revolutionized the world of work and society in the 21st century. Among the most visible changes in the world of work, those related to the organization of work and the emergence of new ways of working stand out. The present study, through an exploratory and qualitative methodology, presents as essential objectives, to identify the main difficulties and challenges that virtual secretariat professionals face in Portugal and to map the main core competencies required of these professionals. This study began with a brief contextualization of the main digital changes and transformations that gave rise to virtual work, followed by an exploration of the key research concept – the virtual Administrative/Executive Secretariat and a survey of the skills required of these professionals. In the next step, semi-structured interviews were conducted with 12 Secretariat professionals working as virtual assistants in Portugal. This study shows that this is an area of action that is already implemented in Portugal and that the pandemic only accelerated a reality that already existed. To thrive, these professionals must increasingly develop their skills to be able to face the challenges and difficulties they have to face. The results also show that the main challenges faced by these professionals are mainly related to the transmission of trust to their clients or employer; definition of working hours; adapting to new clients and being able to “disconnect from work”. The most relevant technical skills, according to the interviewees, were digital knowledge; knowledge of management and organizational communication and the mother tongue. Regarding the most relevant socio-behavioral skills, the following stand out: self-motivation and self-discipline; adaptation to change and the new work environment and organization and work method. This investigation contributes to the study of the profession, making known its most recent form of action – the virtual secretariat.